Analysis of PM1 Concentration on Primary Arterial Roads in Padang City and Correlation with Meteorological Conditions and Traffic Characteristics - Ramadhanil; Vera Surtia Bachtiar; Rizki Aziz (Universitas Negeri Padang, 2025)
This study aims to analyze PM1 concentration and the correlation of PM1 concentration with meteorological conditions and traffic characteristics on Padang City Primary Arterial Roads. The research location is perpendicular to Padang City Bypass II Road which is 5m from the roadside. PM1 measurements were carried out using an EPAM 5000 real-time particulate air monitor. Measurements were made during morning rush hour (06.30-08.30 WIB), midday off-peak hours (11.00-13.00 WIB), and evening rush hour (16.00-18.00 WIB). The results showed that the average PM1 concentration and standard deviation in the morning, midday, and evening were 17.48(3.05) μg/m3, 22.87(2.76) μg/m3, and 34.60(7.68) μg/m3 respectively with the highest concentration obtained in the evening reaching 42.63 μg/m3 and the lowest concentration in the morning 12.83 μg/m3. The results of the correlation between PM1 concentrations and meteorological conditions have a reasonably strong to very strong correlation. PM1 concentrations are directly proportional to temperature and wind speed and inversely proportional to humidity. The correlation results of PM1 concentrations to traffic characteristics are directly proportional, such as traffic volume, vehicle speed, and traffic density have a reasonably strong to very strong correlation. These results indicate meteorological factors and traffic characteristics as the main contributors to road air pollution. The recommendation from this study is to optimize air quality monitoring and traffic management.